The future of seniors housing in situation of demographic aging of the society – preferences of users and directions of changes - Magdziak, Monika (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
Wishing to look deeper into the residential future of seniors, the author tried to identify important global trends influencing the development of the housing environment for the older generation, as well as factors contributing to changes in social service preferences and care requirements. The author examines the issues of Polish demographic and socio-cultural conditions, presents a system of special forms of housing for the elderly and design ideas which have been tested and accepted in other high-developed countries.